Ia antigenic specificities are oligosaccharide in nature: hapten- inhibition studies (The Rockefeller University Press, 1977)
We have previously reported that the Ia specificities, coded for by the I region within the H-2 complex, appear to consist predominantly of carbohydrate. This conclusion was reached by examining low molecular weight Ia-bearing oligosacharides isolated from mouse serum. We now report hapten-inhibition studies which indicate that the binding of both allogeneic and xenogeneic anti-Ia antibodies to the Ia glycoproteins found predominantly on B lymphocytes can be specifically inhibited by certain free sugars. Both inhibition assays revealed that the specificity for the following Ia antigens resides predominantly in the following sugars: (a) Ia.1: N-acetyl-D-mannosamine or related sugars; (b) Ia.3: alpha-D-galactose and related sugars; (c) Ia.7: L- fucose; and (d) Ia.15: N-acetyl-D-glucosamine. It seems likely that these sugars are found at the terminal nonreducing ends of the carbohydrate portion of the Ia-bearing glycoproteins present in the lymphocyte membrane. In contrast, several public and private H-2 antigenic specificities did not appear to be sugar defined. These studies imply that at least some of the Ia genes from both the I-A and I-C subregions of the I region code for glycosyl transferases which modify oligosaccharide structure and impart specificity to the Ia antigens by alteration of their terminal sugar residues.